The Effect of Financial Literacy and Income on Investment Decisions - Agus Yulianto (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This research is a quantitative research with descriptive analysis which aims to determine the effect of financial literacy and income on investment decisions. Good financial financial literacy can help in investment decisions from illegal investments or fraudulent investment portals and thus income becomes a benchmark for the ability to make the best investment decisions for the future. In this study the population is the number of permanent employees at PT. Indotech Scientific with 30 research respondents. Data collection is done by distributing google forms to respondents. The research technique uses non-probability sampling through a purposive sampling approach. In data analysis assisted by using SPSS version 25 . This research applies to multiple regression analysis, t test, F test and coefficient of determination to test financial literacy and income on investment decisions. Based on statistical tests that have been carried out, it is found that financial literacy and income have a positive and significant effect on investment decisions for employees of PT. Indotech Scientific